(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study aims to know how much the effect of organizational communication on the effectiveness of the implementation of development in Palamba Village, South Langowan District. The sample in this study amounted to 60 respondents using quantitative research methods and the instruments of this study were interviews and questionnaires. The data analysis technique used was validity, reliability testing, simple regression analysis and correlation analysis. From the research conducted and data obtained, that organizational communication has a positive influence on the effectiveness of the implementation of development in the Village of Palamba, South Langowan District.